Diagnostic utility of Cytokeratin 13 and Cytokeratin 17 in Oral Epithelial Dysplasia and Oral Squamous Cell Carcinoma - Maryam Nazir Kiani; Muhammad Asif; Fakeha Meraj Ansari; Nighat Ara; Muhammad Ishaque; Amna Riaz Khan (Asian Pacific Journal of Cancer Biology, 2020)
Objective: To determine the immunohistochemical expression of CK 13 and CK 17 in Oral Epithelial Dysplasia and Oral Squamous Cell Carcinoma. Methods: A total of 170 cases were retrieved from record files of Histopathology Department, to conduct a cross sectional study at Armed Forces Institute of Pathology, Rawalpindi, over a period of one year from June 2018 to June 2019 along with their formalin-fixed, paraffin embedded blocks comprising 85 cases of each oral squamous cell carcinoma and oral epithelial dysplasia. Blocks were trimmed and cut into very thin sections of 5 microns using microtome and mounted on slides. Tissue mounted slides were stained with routine haematoxylin and eosin followed by immunohistochemical staining of cytokeratin 13 and cytokeratin 17. New histological diagnosis of each case was made. Mean and standard deviation were calculated for quantitative variables. Frequency and percentages were calculated for qualitative variables. Chi-square test was employed to assess the significance of difference. The P-value <0.05 was considered significant. Results: In this study, 101 (59.4%) male and 69 (40.6%) female patients with the mean age of 60.63 ± 13.814 (mean ± SD) were collected and buccal mucosa was the most common site of presentation. In a total of 170 cases, 34 (20%) cases showed positive expression of cytokeratin 13 whereas 136 (80%) cases showed negative expression of cytokeratin 13. In comparison, out of 170 cases, 133 (78.2%) cases showed positive expression of cytokeratin 17 whereas 37 (21.8%) cases showed negative expression of cytokeratin 17. The P-value was found to be < 0.001 and 0.001 for expression of cytokeratin 13 and cytokeratin 17 respectively. Conclusion: Opposite expression of cytokeratin 13 and cytokeratin 17 was seen in this study, in the form of loss of cytokeratin 13 and over expression of cytokeratin 17 with increase in the degree of dysplasia and invasive carcinoma. Correct assessment, diagnosis and management with the help of these markers can lead to early diagnosis and favorable treatment outcome.